Upper Eocene elasmobranch assemblages from Myanmar: Evidence for the easternmost dispersal pathways across the Neotethys - Sylvain Adnet; Xavier Valentin; Yaowalak Chaimanee; Aung Naing Soe; Chit Sein; Jean-Jacques Jaeger (Palaeoworld, 2026)

New late middle Eocene anthropoids from Dur At-Talah, Libya: Implications for early primate dispersal into Afro-Arabia - Jean-Jacques Jaeger; Yaowalak Chaimanee; Mouloud Benammi; Laurent Marivaux; Olivier Chavasseau; K. Christopher Beard; Xavier Valentin; Osama Hlal; Awad Bilal; Pauline Coster; Michel Brunet (Journal of Human Evolution, 2026)

Correlates of pregnant women’s active and passive mobility: A smartphone-based tracking study in Barcelona, Spain - Karl Samuelsson; Ioar Rivas; Marta Cirach; Bruno Raimbault; Alan Domínguez; Yu Zhao; Toni Galmés; Antònia Valentin; Maria Foraster; Mireia Gascon; Cecilia Persavento; Maria Dolores Gomez Roig; et al. (Travel Behaviour and Society, 2026)

Hybodont shark remains from Campanian (Upper Cretaceous) continental deposits of southern France - Xavier Valentin; Romain Vullo; Gilles Cuny; Olivier Jansen; Géraldine Garcia (Cretaceous Research, 2026)

Abrupt changes in continental sedimentation triggered by monsoon-type event during EECO hyperthermals, Minervois Basin, Southern France - Cindy BOYRIE; Flavia GIRARD; Johan YANS; Grégory BALLAS; Fabrice LIHOREAU; Mouloud BENAMMI; Hélène BOURGET; Géraldine GARCIA; Christine LEREDDE; Aimée PELLISSIER-TANON; Xavier VALENTIN; Dominique VIDALENC; et al. (Sedimentary Geology, 2025)

Impact of the EECO on mammalian faunas: New Ypresian localities from Montpellier (France), a multidisciplinary approach - Fabrice Lihoreau; Johan Yans; Mouloud Benammi; Flavia Girard; Gregory Ballas; Hélène Bourget; Cindy Boyrie; Jacinthe Caillaud; Anne-Lise Charruault; Killian Gernelle; Floréal Solé; Xavier Valentin; et al. (Proceedings of the Geologists' Association, 2025)

Tree inventory data from permanent plots in F rench forest reserves - Eugénie Cateau; Nicolas Debaive; Nicolas Drapier; Flavien Chantreau; Olivier Gilg; Fabien Laroche; Xavier Morin; Valentin Demets; Raúl Pimenta; Lucie Thompson; Yoan Paillet (Ecology, 2024)
We present a data set resulting from the first round of a national monitoring program of forest reserves. It contains 9538 permanent plots, distributed across 111 study sites in mainland France (including Corsica). Notably focusing on dead wood measurement, this protocol has primarily been applied in strict forest reserves and special nature reserves (sensu Bollmann & Braunisch 2013), with 68% (6494) of the plots being currently located in strict forest reserves (unmanaged) and 24.7% (2363 plots) in forests unmanaged for at least 50 years. Sites cover a large variety of ecological conditions, from lowland to subalpine forests, but with an underrepresentation of Mediterranean forests (Table 1). The protocol assesses all the stages of a tree's life cycle, from seedling to decomposed lying dead wood. On each plot, a combination of three sampling techniques was used: (1) fixed‐area inventory for regeneration, standing dead trees, living trees, and coarse woody debris (CWD) with diameter over 30 cm; (2) transect lines for CWD with diameter 30 cm (using a relascopic angle of 3%). Measurements include exact tree location (azimuth, distance), species, diameter(s), tree‐related microhabitats, decay stage and bark cover, and seedling cover. With ongoing climate change, the program network can also provide important information to monitor changes in forest ecosystems. It can also be used as forest management monitoring or conservation status assessment. These data are freely available for noncommercial scientific use (Creative Commons Attribution 4.0 CC BY SA 4.0) with attribution, and this paper must be cited if this material is reused.

The rodent fauna from Prat de Cest (Aude, France) and its biochronological implications for the Early Miocene - Vincent Luccisano; Xavier Valentin; Géraldine Garcia; Vincent Lazzari (Geobios, 2024)

First international workshop of the ATM and cancer risk group (4-5 December 2019) - Fabienne Lesueur; Douglas F. Easton; Anne-Laure Renault; Sean V. Tavtigian; Jonine L. Bernstein; Zsofia Kote-Jarai; Rosalind A. Eeles; Dijana Plaseska-Karanfia; Lidia Feliubadaló; Alejandro Moles-Fernández; Marta Santamariña-Pena; Alysson T. Sánchez; et al. (Familial Cancer, 2022)

Obesity of mice lacking VAP-1/SSAO by Aoc3 gene deletion is reproduced in mice expressing a mutated vascular adhesion protein-1 (VAP-1) devoid of amine oxidase activity - Valentin Jargaud; Sandy Bour; François Tercé; Xavier Collet; Philippe Valet; Anne Bouloumié; Jean-Claude Guillemot; Pascale Mauriège; Sirpa Jalkanen; Craig Stolen; Marko Salmi; David J. Smith; et al. (Journal of Physiology and Biochemistry, 2021)

Correlative climatic niche models predict real and virtual species distributions equally well - Valentin Journé; Jean‐Yves Barnagaud; Cyril Bernard; Pierre‐André Crochet; Xavier Morin (Ecology, 2020)
Climate is one of the main factors driving species distributions and global biodiversity patterns. Obtaining accurate predictions of species’ range shifts in response to ongoing climate change has thus become a key issue in ecology and conservation. Correlative species distribution models ( cSDM s) have become a prominent tool to this aim in the last decade and have demonstrated good predictive abilities with current conditions, irrespective of the studied taxon. However, cSDM s rely on statistical association between species’ presence and environmental conditions and have rarely been challenged on their actual capacity to reflect causal relationships between species and climate. In this study, we question whether cSDM s can accurately identify if climate and species distributions are causally linked, a prerequisite for accurate prediction of range shift in relation to climate change. We compared the performance of cSDM s in predicting the distributions of 132 European terrestrial species, chosen randomly within five taxonomic groups (three vertebrate groups and two plant groups), and of 1,320 virtual species whose distribution is causally fully independent from climate. We found that (1) for real species, the performance of cSDM s varied principally with range size, rather than with taxonomic groups and (2) cSDM s did not predict the distributions of real species with a greater accuracy than the virtual ones. Our results unambiguously show that the high predictive power of cSDM s can be driven by spatial autocorrelation in climatic and distributional data and does not necessarily reflect causal relationships between climate and species distributions. Thus, high predictive performance of cSDM s does not ensure that they accurately depict the role of climate in shaping species distributions. Our findings therefore call for strong caution when using cSDM s to provide predictions on future range shifts in response to climate change.

Erratum to: First record of a diacodexeid artiodactyl in the middle Eocene Pondaung Formation (Myanmar) - Stéphane Ducrocq; Aung Naing Soe; Chit Sein; Vincent Lazzari; Yaowalak Chaimanee; Xavier Valentin; Jean-Jacques Jaeger (PalZ, 2016)

First record of a diacodexeid artiodactyl in the middle Eocene Pondaung Formation (Myanmar) - Stéphane Ducrocq; Aung Naing Soe; Chit Sein; Vincent Lazzari; Yaowalak Chaimanee; Xavier Valentin; Jean-Jacques Jaeger (PalZ, 2016)

Ichthyosaurs from the French Rhaetian indicate a severe turnover across the Triassic–Jurassic boundary - Valentin Fischer; Henri Cappetta; Peggy Vincent; Géraldine Garcia; Stijn Goolaerts; Jeremy E. Martin; Daniel Roggero; Xavier Valentin (The Science of Nature, 2014)

Intriguing small-scale spatial distribution of chloropastic and nuclear diversity in the endangered plant Biscutella neustriaca (Brassicaceae) - Jean-Baptiste Leducq; Céline Siniarsky; Celia Chantal Gosset; Cécile Godé; Matthieu Poiret; Christophe Blondel; Nina-Coralie Hautekèete; Yves Piquot; Céline Poux; Bertille Valentin; Sylvain Billiard; Xavier Vekemans (Conservation Genetics, 2013)

Gaudeamus lavocati sp. nov. (Rodentia, Hystricognathi) from the early Oligocene of Zallah, Libya: first African caviomorph? - Pauline Coster; Mouloud Benammi; Vincent Lazzari; Guillaume Billet; Thomas Martin; Mustafa Salem; Awad Abolhassan Bilal; Yaowalak Chaimanee; Mathieu Schuster; Xavier Valentin; Michel Brunet; Jean-Jacques Jaeger (The Science of Nature, 2010)